Prestack seismic data regularization using a time-variant anisotropic Radon transform. (7th June 2016) - Gong, Xiangbo; Yu, Shuang; Wang, Shengchao
Abstract: The Radon transform (RT) has been widely used in seismic data processing. In this paper, we develop a sparse time-variant anisotropic Radon transform (ART) to regularize and interpolate the prestack seismic data. By introducing the anelliptical parameter η, the ART has a more accurate integral path than other widely used RTs, which produces a better energy-focused Radon panel in the case of a vertical transverse isotropy VTI medium or seismic gather with a large moveout. To promote the sparsity of the Radon panel, the RT is realized as a l 1 – l 2 norm inversion problem, and the fast iterative shrinkage thresholding algorithm is imposed to solve this sparsity-constrained inversion problem. Compared with the time-invariant parabolic RT in the mixed frequency-time domain and time-variant hyperbolic RT, the reconstructed result of the ART has the best performance and the least reconstruction error in a general synthetic VTI medium. Another field marine example further demonstrates that the ART is effective and robust for prestack seismic data regularization.